2007
DOI: 10.1149/1.2798668
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Electrodeposition from a Room Temperature Eutectic Melt

Abstract: This paper discusses recent results from the authors' lab dealing with nickel electrodeposition from a choline chloride/urea eutectic melt (molar ratio 1:2). The temperature dependence of the viscosity of the melt was investigated with the quartz crystal microbalance (QCM). It has been found that with increasing nickel content the viscosity of the electrolyte increases and that the melt shows viscoelastic behavior up to ca. 60{degree sign}C. Using the QCM in the electrochemical mode (EQCM) the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…4). It was shown that EQCM can approximate quite well viscosities of deep-eutectic solvents at higher temperatures (10). However, for the deep-eutectic solvents at lower temperatures one usually obtains discrepancies between the values calculated from the EQCM data and those obtained with a traditional technique, like a rotational viscosimeter.…”
Section: Resultsmentioning
confidence: 99%
“…4). It was shown that EQCM can approximate quite well viscosities of deep-eutectic solvents at higher temperatures (10). However, for the deep-eutectic solvents at lower temperatures one usually obtains discrepancies between the values calculated from the EQCM data and those obtained with a traditional technique, like a rotational viscosimeter.…”
Section: Resultsmentioning
confidence: 99%
“…Timeline of DES exploration of specific applications. Solvent properties of DES, [30] carboxylic acid with ChCl DES properties, [31] ionothermal materials synthesis, [32] nickel electrodeposition, [33] biocatalytic application, [34] drug solubilization, [35] synthesis of photoluminescence and photochromisn, [36] enzyme activation, [37] synthesis of polymer and related materials, [38] natural DES for extraction of phenolic metabolites, [39] electrolytic function for supercapacitors [40] and application in nanotechnology, [41] tailoring properties of DES with water [42] and solvent for separation, [43] organocatalytic-biotransformation activity of DES, [44] application in biotechnology, [45] bio-inspired electrolyte for LIBs, [46] biomass pretreatment using DES, [47] theuraputic application, [48] and separation of quazrt and magnetie. [49] provides a summary of initial DESs applied in different topics by time.…”
Section: History Of Deep Eutectic Solvents (Des)mentioning
confidence: 99%
“…[49] provides a summary of initial DESs applied in different topics by time. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Generally, DESs are formed when the donor and the acceptor of compounds are bound by hydrogen bond at ambient temperature in a liquid state. A variety of common hydrogen donors and acceptors for the preparation of DESs were exhibited in Figure 2.…”
Section: History Of Deep Eutectic Solvents (Des)mentioning
confidence: 99%
“…Moreover, the wave (R 3 ) was attributed to a cathodic breakdown of the DES that is catalysed by the Ni NPs deposited beforehand on the surface of the electrode. [16][17][18][19]39 N i the amount of water (up to 7.51 wt%) enhances the currents of the waves R" 1 (onset at E = −0.18 V for the blue curve) and R" 2 (onset at E = −0.67 V for the blue curve) and decreases drastically the potential window (purple and blue curves). First tentative assignment of these two processes could be to the adsorption of water on the polycrystalline nickel electrode 3,55 (eq.…”
Section: And 2)mentioning
confidence: 99%
“…14,15 For these reasons, the number of publications on electrodeposition from DES is spectacularly increasing, notably for nickel. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The electrodeposition from these non-aqueous baths have proven successful to obtain nickel coatings, [18][19][20]34 nickel-based alloys 21,22,24,25,27,28,35 and nanostructured nickel films for corrosion resistance. 29,30 Similarly, DES were also used for the synthesis of a multitude of nanostructures (Pd, 36 Au, 37 ...), due to the capability of these solvents to slow down the electrochemical processes, thus, having a better control of the deposition of nanostructures.…”
Section: Introductionmentioning
confidence: 99%